2014
DOI: 10.1167/iovs.14-15225
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Imaging of Enzymatic Vitreolysis-Induced Fiber Remodeling

Abstract: Proteoglycan loss due to enzymatic vitreolysis differentially increases fiber alignment at locations where tractions are most common. We hypothesize that a similar mechanism leads to retinal complications during age-related vitreous degeneration. Structural changes to the entire vitreous body (as opposed to the vitreoretinal interface alone) should be evaluated during preclinical testing of pharmacological vitreolysis candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
(69 reference statements)
1
7
0
Order By: Relevance
“…We theorize that the confocal system is necessary to powerfully reduce speckle noise due to inherently weak signal of vitreous fibers. The inherently weak signal likely also explains why we were unable to image vitreous with second harmonic generation microscopy, even when using an ultra-sensitive, refractiveindex-matched substage detector [22], and why Filas et al were not able to image individual fibers with quantitative polarized light microscopy [18]. They were able to extract measures of average alignment and orientation, and found poor alignment, consistent with our findings.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…We theorize that the confocal system is necessary to powerfully reduce speckle noise due to inherently weak signal of vitreous fibers. The inherently weak signal likely also explains why we were unable to image vitreous with second harmonic generation microscopy, even when using an ultra-sensitive, refractiveindex-matched substage detector [22], and why Filas et al were not able to image individual fibers with quantitative polarized light microscopy [18]. They were able to extract measures of average alignment and orientation, and found poor alignment, consistent with our findings.…”
Section: Discussionsupporting
confidence: 86%
“…Based on the generally anterior-posterior orientations that Filas et al observed by quantitative polarized light microscopy [18] along the anterior-posterior axes originating at the nasal and temporal limbus, we anticipated that we would find angular means around 0 degrees, which we defined as parallel to the anterior-posterior axis. Although the angular means in the nasal-radial dataset were closer to zero, the angular means in the remaining 4 tangential datasets were widely distributed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Jan et al, 2017a; Jan et al, 2015; Jan et al, 2017b) It has been shown that the PLM signal correlates with the orientation of collagen fibers. (Bromage et al, 2003; Diamant et al, 1972; Keikhosravi et al, 2017) In addition, PLM has been used extensively for quantifying crimp in other tissues, such as the vitreous, (Filas et al, 2014) tendon (Diamant et al, 1972; Franchi et al, 2007; Hansen et al, 2001) and ligament. (Boorman et al, 2006; Shah et al, 1977)…”
Section: Discussionmentioning
confidence: 99%